Strategy for Detection and High-Resolution Characterization of Authigenic Carbonate Cold Seep Habitats Using Ships and Autonomous Underwater Vehicles on Glacially Influenced Terrain - Thorsnes, Terje; Chand, Shyam; Brunstad, Harald; Lepland, Aivo; Lågstad, Petter (Frontiers in Marine Science, 2019)
Cold seep habitats with authigenic carbonates and associated chemosynthetic communities in glacially-influenced terrains constitute an important part of the benthic ecosystems, but they are difficult to detect in large-scale seabed surveys. The areas they occupy are normally small, and survey platforms and sensors allowing high-resolution spatial characterization are necessary. We have developed a cold seep habitat mapping strategy that involves both ship and autonomous underwater vehicle (AUV) as platforms for multibeam echosounder, synthetic aperture sonar and a digital photo system. Water column data from the shipborne multibeam echosounder data are initially used to detect gas flares resulting from fluid flow from the seabed. The next phase involves mapping of flare areas by synthetic aperture sonar, mounted on an AUV. This yields an acoustic image with a resolution up to 2 cm over a swath of c. 350 metres, allowing detection of seep-related features on the seabed. The last phase involves digital photographing of the seabed, with the AUV moving close to the seabed, allowing recognition of bubble streams, seep-related features and giving a first order documentation of the fauna. The strategy was applied to a 3775 km2 large area on the continental shelf, northern Norway. This is a passive continental margin, with thick deposits of oil- and gas-bearing sedimentary rocks. Extensive faulting and tilting of layers provide potential conduits for fluid flow. The seabed is glacially influenced with a highly-variable backscatter reflectivity. More than 200 gas flares have been identified, and a similar number of cold seep habitats have been characterized in high spatial detail. Two case studies are shown. In the first area, there is a close spatial relation between active gas seepage and carbonate crust fields. The second case study shows that carbonate crust fields are not necessarily spatially associated with currently active seeps, but represent dormant or formerly active gas expulsion. An important finding is that the bathymetric resolution of shipborne multibeam echosounders will often be too low to detect cold seep habitats. This means that a nested multi-resolution approach involving a multitude of platforms and sensors is required to provide the full picture.